Seismic Performance Evaluation of Shape Memory Alloy (SMA) Reinforced Concrete Bridge Bents Under Long-Duration Motion - Rahman, Jesika; Billah, A. H. M. Muntasir (Frontiers in Built Environment, 2020)
The emergence of the Shape Memory Alloy (SMA) rebar has paved the way towards resilient bridge design through improved post-earthquake functionality. The focus of this study is to numerically examine the effects of SMA rebar inclusion on the seismic performance of a reinforced concrete (RC) bridge bent under long-duration motions and perform a comparative analysis with the conventional steel-reinforced bridge bent. The duration effect is examined by assembling a pair of forty long-duration and spectrally equivalent short duration motions, without considering the pulse-nature of ground motions. Three different reinforcement configurations, with and without SMA rebar in the bridge bent bottom and top plastic hinge, are considered here. Using the selected ground motions, incremental dynamic analysis (IDA) is conducted to examine the duration effect considering different performance indicators such as maximum drift and residual drift. For residual drift, the dominance of ground motion duration is observed which is found to have a lesser impact on the SMA reinforced bents. The detrimental effect of long-duration motion is more pronounced for the steel-reinforced bridge bent compared to the SMA reinforced bents.